2020
DOI: 10.25174/2582-2675/2020/100835
|View full text |Cite
|
Sign up to set email alerts
|

Stable sources of resistance to yellow rust and powdery mildew in Indian and exotic wheat germplasm

Abstract: Yellow rust (Puccinia striiformis f. sp. tritici) and powdery mildew (Blumeria graminis tritici) of wheat can be effectively managed by the cultivation of resistant varieties. However, such resistant varieties become susceptible due to evolution and spread of new and matching virulences of these pathogens after a short period of their commercial cultivation. Hence, breeding for disease resistance tends to be a continuous process with prerequisite of identification of diverse resistant donors. In this context, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
1
0
1
Order By: Relevance
“…Genotype 'Maris Dove' showed mean TDS of ≤10 for PM and YR. Genotypes ALDAN, CMH 77.308, SAW 71 and SAW 74 with mean TDS ≤15 for PM and YR, at all the locations, were moderately resistant to both the diseases (Table 4). The present results of combined resistance to PM and YR have been corroborated by reports of combined resistance to leaf and yellow rust (Kochumadhavan et al 1980;Shrestha and Mahto 2021), PM and YR (Sood et al 2020;Vikas et al 2019). Among loose smut (LS) differential no genotypes was found resistant to PM whereas, TD 1 (Mindum), TD 2 (Renfrew) and TD 4 (Kota) showed YR severity <10S.…”
Section: Multiple Disease Resistance Genotypessupporting
confidence: 91%
See 2 more Smart Citations
“…Genotype 'Maris Dove' showed mean TDS of ≤10 for PM and YR. Genotypes ALDAN, CMH 77.308, SAW 71 and SAW 74 with mean TDS ≤15 for PM and YR, at all the locations, were moderately resistant to both the diseases (Table 4). The present results of combined resistance to PM and YR have been corroborated by reports of combined resistance to leaf and yellow rust (Kochumadhavan et al 1980;Shrestha and Mahto 2021), PM and YR (Sood et al 2020;Vikas et al 2019). Among loose smut (LS) differential no genotypes was found resistant to PM whereas, TD 1 (Mindum), TD 2 (Renfrew) and TD 4 (Kota) showed YR severity <10S.…”
Section: Multiple Disease Resistance Genotypessupporting
confidence: 91%
“…The present results have been corroborated by the earlier reports(Yang et al 2017;Vikas et al 2020;Sood et al 2020) of wheat genotypes with multiple resistance to various diseases including PM and YR. In the present studies, genotypes with multiple resistance to PM and YR have been identified and incidentally some genotypes have been reported to have proven resistance to other important prevailing diseases like Karnal bunt and loose smut.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…La identificación de fuentes de resistencia sigue siendo un reto para fitopatólogos y mejoradores; afortunadamente, en México se han identificado fuentes con genes de resistencia de raza específica a roya amarilla y se han incorporado a variedades con alto potencial de rendimiento, como es el caso de los genes Yr5, Yr15 y Yr17 en la variedad Borlaug 100 (Valdez-Rodríguez et al, 2020) o se han desarrollado genotipos con resistencia en planta adulta, como en el presente estudio, donde se observó que al menos 70 % de las líneas tuvieron niveles aceptables de resistencia. En países como Pakistán, India y Egipto (Badoni et al, 2017;Elbasyoni et al, 2019;Rehman et al, 2019;Sood et al, 2020) se han identificado fuentes de resistencia a las razas prevalentes en esos países. Estas líneas incluyen resistencia de raza específica y resistencia parcial de planta adulta, como es el caso de las líneas evaluadas en el presente estudio.…”
Section: Diferencialunclassified